2020
DOI: 10.1097/md.0000000000021491
|View full text |Cite
|
Sign up to set email alerts
|

Th17/Treg imbalance in patients with severe acute pancreatitis

Abstract: Background: To investigate the effect of high-volume hemofiltration (HVHF) on Th17/Treg imbalance in patients with severe acute pancreatitis (SAP). Methods: Forty-two patients with SAP were randomly received 24 hours of continuous HVHF (n = 21) or without HVHF (n = 21). At day 28, all 42 patients were divided into survival group (n = 32) and non-survival group (n = 10). Venous blood samples collected at 0, 6, 12, and 24 hours during HVHF treatment (or equivalent time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The imbalance between Th17 cells and Tregs is common and relevant to the severity and prognosis of AP. Recent study confirmed that the proportion of Th17/Treg was significantly higher in SAP patients and more pronounced in the multiple organ failure group (P<0.05) (113). The homeostasis of the pancreatic microenvironment and rapid response to invaders are tightly regulated by the continuous adjustment between harmful Th17 cells and immunosuppressive Tregs, which establishes an ecological niche for bacterial intestinal border-dwelling bacteria (114).…”
Section: Microbiota-propelled T Helper 17 Cells In Apmentioning
confidence: 87%
See 1 more Smart Citation
“…The imbalance between Th17 cells and Tregs is common and relevant to the severity and prognosis of AP. Recent study confirmed that the proportion of Th17/Treg was significantly higher in SAP patients and more pronounced in the multiple organ failure group (P<0.05) (113). The homeostasis of the pancreatic microenvironment and rapid response to invaders are tightly regulated by the continuous adjustment between harmful Th17 cells and immunosuppressive Tregs, which establishes an ecological niche for bacterial intestinal border-dwelling bacteria (114).…”
Section: Microbiota-propelled T Helper 17 Cells In Apmentioning
confidence: 87%
“…Researchers found that continuous veno-venous hemofiltration (CVVH) removed IL-17 and other proinflammatory cytokines from serum, improved intestinal barrier function, and relieved systemic reactions. In addition, high-volume hemofiltration (HVHF) effectively attenuated the Th17/Treg imbalance during SAP ( 113 ). The Th17/Treg ratio and IL-17 were significantly reduced ( P <0.05) after HVHF, while no significant change was found in the non-HVHF group.…”
Section: Therapeutic Implications Of Apmentioning
confidence: 99%
“…It has been reported that dysregulation of immune responses may lead to the progression of AP (21,22). Guo et al (23) highlighted that the T helper 17 (Th17) cell/regulatory T cell (Treg) imbalance was involved in the development of AP and that it may be correlated with its severity and prognosis (24). Therefore, Treg cells play a key role in mediating the progression of AP.…”
Section: Emodin Inhibits the Progression Of Acute Pancreatitis Via Regulation Of Lncrna Tug1 And Exosomal Lncrna Tug1mentioning
confidence: 99%
“…The results suggested that the changes in cytokines could also be affected by other intestinal immune cells such as Peyer’s patches, which will be our future research direction. Tregs exert immunosuppressive effects by inhibiting INF-γ secretion and promoting IL-4, IL-10, and TGF-β secretion ( 64 , 65 ). A study has proved that Tregs were decreased and inversely associated with the serum concentration of TNF-α in SAP mice ( 66 ).…”
Section: Discussionmentioning
confidence: 99%